The Influence of The Implementation of the Attendance Face Recognition System and Punishment on the Discipline of Employees of the Social Service of Palembang City - Artiyas Nur’an Najmi; Siti Komariah Hildayanti; Emilda Emilda (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the effect of face recognition system attendance and punishment on the work discipline of Palembang City Social Service employees. The research method used is a quantitative research method, with a population of all PNS employees at the Palembang City Social Service Office totaling 39 employees. Data collection techniques were carried out by interviews and questionnaires. The data analysis technique used SPSS version 26. The results showed that the t-count variable for applying face recognition attendance ( )) was 2.465 with a significant value of 0.019 <0.05, so it could be concluded that partially there was a significant effect between facial recognition attendance on employee work discipline at the Palembang City Social Service. For the punishment variable ( ) it shows that the tcount is 2.410 with a significant value of 0.021 <0.05, which means that partially there is a significant influence between punishment on employee work discipline at the Palembang City Social Service. The results of testing the F test hypothesis obtained a significant value of 0.001 <0.05, so the hypothesis was accepted, it could be interpreted that the presence of face recognition and punishment simultaneously had a significant effect on employee work discipline at the Social Services Office of Palembang City by 48.1%.